2022
DOI: 10.1088/1361-6463/ac7e84
|View full text |Cite
|
Sign up to set email alerts
|

Annealing temperature dependence of band alignment of NiO/β-Ga2O3

Abstract: The band alignment of sputtered NiO on β-Ga2O3 was measured by x-ray photoelectron spectroscopy for post-deposition annealing temperatures up to 600 °C. The band alignment is type II, staggered gap in all cases, with the magnitude of the conduction and valence band offsets increasing monotonically with annealing temperature. For the as-deposited heterojunction, ΔE V = −0.9 eV and ΔE C = 0.2 eV, while after 600 °C annealing the corresponding values are ΔE V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 40 publications
2
37
0
Order By: Relevance
“…In our estimate, the change in bandgap for the NiO x layer between 300 and 400 K is less than 0.1 eV (E g (300 K) = 3.84 eV and E g (400 K) = 3.76 eV). [52] A recent study has shown that rapid thermal annealing of NiO x /𝛽-Ga 2 O 3 heterojunction diodes can provide significant improvement in the quality of the p-n diode interface, accompanied by a decrease in the interfacial defect states acting as recombination centers. [53] In the reported study, annealing was performed at 225 °C in an N 2 atmosphere to improve Ga 2 O 3 /NiO interface quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our estimate, the change in bandgap for the NiO x layer between 300 and 400 K is less than 0.1 eV (E g (300 K) = 3.84 eV and E g (400 K) = 3.76 eV). [52] A recent study has shown that rapid thermal annealing of NiO x /𝛽-Ga 2 O 3 heterojunction diodes can provide significant improvement in the quality of the p-n diode interface, accompanied by a decrease in the interfacial defect states acting as recombination centers. [53] In the reported study, annealing was performed at 225 °C in an N 2 atmosphere to improve Ga 2 O 3 /NiO interface quality.…”
Section: Resultsmentioning
confidence: 99%
“…In our estimate, the change in bandgap for the NiO x layer between 300 and 400 K is less than 0.1 eV ( E g (300 K) = 3.84 eV and E g (400 K) = 3.76 eV). [ 52 ]…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16][17] Both types can conduct 4100 A cm À2 at 4 V. Note that the R ON in the heterojunction rectifiers does not continue to decrease at forward voltages beyond B3 V. It has also been shown that the band alignment remains type II, staggered gap with the magnitude of the conduction and valence band offsets increasing monotonically with annealing temperature. 12 Fig. 3 shows the reverse J-V characteristics for both types of devices at different temperatures.…”
Section: Methodsmentioning
confidence: 99%
“…1,3,4 To achieve a high-power figure of merit, a rectifier must have a low drift layer concentration, with high electron mobility, as well as low R ON , and optimized edge termination to prevent current crowding. 1,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The breakdown voltage is larger for thicker drift layers, but this degrades the on-resistance. In addition, vertical geometry devices are desirable, because of their higher power conversion efficiency and absolute currents compared to lateral devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation